Tourism well-being and transitioning Island destinations for sustainable development - Jerome Agrusa; Cathrine Linnes; Joseph Lema; Jihye (Ellie) Min; Tony L. Henthorne; Holly Itoga; Harold Lee (Journal of Risk and Financial Management, 2021)
The unprecedented growth of tourism over the last century has led to increasing concerns over the sustainable development of many popular tourism destinations throughout the globe. High concentrations of tourists and residents, especially in urbanized areas, have heightened this concern with the arrival of the novel coronavirus (COVID-19) pandemic. Over reliance on tourism has left residents vulnerable to external factors, such as the coronavirus pandemic that has halted tourists from coming to this remote destination. As a result, Hawaii's overall economy is suffering greatly. A survey was developed and distributed to potential tourists in order to acquire their perceptions regarding tourism and well-being, as well as the COVID-19 outbreak. The focus of this study was to examine practices in tourism that moves beyond solely economics which will allow repositioning in a manner that promotes the well-being of both residents and tourists and to transition this unique tourism destination for sustainable development practices for the future. One of the results from the study reported that the majority of the respondents agreed or strongly agreed that testing for COVID-19 should be a travel requirement prior to flying to Hawaii, as well as having an additional COVID-19 test administered upon arrival.
Keywords: 330; COVID-19; island tourism; sustainable development; well-being; community impact